Toward a Systematic Understanding of "Heaviness" in Metal Music Production - Herbst, Jan-Peter; Mynett, Mark (Rock music studies, 2023)
"Heaviness" has been one of metal music's defining features in three decades of metal scholarship. Research acknowledged its essential quality, but no comprehensive definition of musical heaviness was developed. This article, therefore, elaborates a preliminary framework of musical heaviness by identifying its constituent production, performance, and compositional components, including their relationships. The findings suggest that while structural and performative components provide the necessary foundation for heaviness, metal has been increasingly driven by its production. Since musicians reach limits, technology has become one of the primary means to produce ever heavier metal music in the genre-defining quest for greater heaviness.